The Father's Parenting Involvement and Adolescent Resilience in Families with Working Spouses in Depok City - Berti Kumalasari; Eko Yuliarti Siroj; Husnayaini Hawari Yunus (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Optimal parenting is an important key to building adolescent resilience. Societal culture tends to exclude fathers from parenting. At the same time, the father's involvement in parenting has a positive effect on adolescent development. This study aims to analyze the father's parenting involvement and adolescents' resilience in families where both husband and wife work. This study used a descriptive qualitative phenomenological method with a purposive sampling technique. There were 15 respondents in this study with the criteria of adolescent children with working fathers and mothers. This research was conducted in Depok City in June 2023. Data collection techniques using in-depth interviews with data analysis, reduction, presentation, and conclusion drawing. The results showed that adolescents whose fathers are directly involved in parenting, care, and pay attention to adolescents and do not conflict with adolescents tend to have high resilience, indicated by being adaptable, not easily angry, and having adequate social support from family, friends, and teachers at school. This study is expected to provide input for relevant institutions and agencies to start campaigning for the importance of fathers' involvement in parenting in order to increase adolescent resilience.